PENGARUH KOMPETENSI, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH DI KABUPATEN PUNCAK JAYA - WONDA, TEKILES; ILHAM, ILHAM (Patria Artha Management Journal, 2025)
This research seeks to examine the influence of competence, motivation and work discipline on employee performance at the Puncak Jaya Regency Regional Financial and Asset Management Agency. This research uses a quantitative methodology using multiple linear regression to determine the influence of the three independent variables (competence, motivation and work discipline) on the dependent variable (employee performance). Information was collected by sending questionnaires to staff, while assessing the validity and reliability of the tools used. Statistical software was used for data analysis to evaluate the developed hypotheses. Multiple linear regression analysis assesses the influence of each independent variable on employee performance, while the F test tests the joint influence of these three variables on employee performance. The results of the analysis show that competence greatly influences employee performance, this shows that increasing individual abilities can improve the quality of work. Therefore, the main focus of the organization should be on employee development and training. On the other hand, motivation does not have much of an impact on performance, but it is still important for organizations to uphold employee morale. Work discipline is proven to have the greatest and most important influence on employee performance, this shows that employees with a strong sense of discipline often show superior work performance. It is recommended that organizations foster a culture of discipline to increase employee efficiency and productivity. In general, competence, motivation and work discipline together improve employee performance at the Puncak Jaya Regency Regional Financial and Asset Management Agency.